2005
DOI: 10.4049/jimmunol.175.11.7661
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Ischemia/Reperfusion Injury Involves Functional TLR4 Signaling in Nonparenchymal Cells

Abstract: Endogenous ligands from damaged cells, so-called damage-associated molecular pattern molecules, can activate innate immunity via TLR4 signaling. Hepatic warm ischemia and reperfusion (I/R) injury and inflammation is largely TLR4 dependent. We produced TLR4 chimeric mice to assess whether the TLR4-dependent injury required TLR4 expression on liver parenchymal or nonparenchymal cells. Chimeric mice were produced by adoptive transfer of donor bone marrow cells into irradiated recipient animals using reciprocal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
287
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(306 citation statements)
references
References 47 publications
13
287
0
6
Order By: Relevance
“…It was further demonstrated that TLR4 on Kupffer cells rather than parenchyma cells, was critical for hepatic IRI. 22 This is in agreement with our own in vitro studies 23 in which macrophages but not hepatocytes responded directly to lipopolysaccharide by producing proinflammatory macrophage/neutrophil-targeted (CXCL1, CCL2) and T cell-targeted (CXCL9, 10, 11) chemokines. Interestingly, however, hepatocytes did respond to TLR4 activation indirectly via macrophage-derived type I IFN, as evidenced by CXCL10 expression.…”
Section: Discussionsupporting
confidence: 90%
“…It was further demonstrated that TLR4 on Kupffer cells rather than parenchyma cells, was critical for hepatic IRI. 22 This is in agreement with our own in vitro studies 23 in which macrophages but not hepatocytes responded directly to lipopolysaccharide by producing proinflammatory macrophage/neutrophil-targeted (CXCL1, CCL2) and T cell-targeted (CXCL9, 10, 11) chemokines. Interestingly, however, hepatocytes did respond to TLR4 activation indirectly via macrophage-derived type I IFN, as evidenced by CXCL10 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Work from the Kupiec-Weglinski group (27,28) examining a model of ischemia/reperfusion liver injury demonstrated that TLR4 signaling, but not TLR2 signaling, was required for optimal inflammatory responses to this insult. Using a similar model, Tsung et al (29) show that functional TLR4 on hemopoietic-derived phagocytes, but not organ parenchymal cells, was required for inflammation associated with liver ischemia/reperfusion. Several studies have focused on the specific products of necrotic cells or extracellular matrix disruption as a source of danger signals, particularly through TLR2-and TLR4-dependent responses (9,30).…”
Section: Injury and Endogenous Danger In Transplantationmentioning
confidence: 99%
“…The signaling transduction of TLR4 results in activation of p38 MAPK and NF-κB, which plays a significant role in the immune cell recruitment and function (Maung et al, 2005;Tsung et al, 2005;Yang et al, 2007). Both p38 MAPK and NF-κB are crucial to the signaling pathway that leads to the proinflammatory cytokine production (Baldwin, 1996;Raingeaud et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is the dominant mammalian receptor for the microbial product lipopolysaccharide (LPS) (Qureshi et al, 1999). TLR4-deficient mice were found to be less prone to hepatic ischemia/reperfusion injury (Tsung et al, 2005) and the expression of TLR4 mRNA and protein was increased in rat Kupffer cells following ischemia/ reperfusion injury (Peng et al, 2004). Moreover, activation of TLR4 initiates an inflammatory cascade in macrophages, involving activation of p38 mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K), and activation of nuclear factor-κB (NF-κB) (Arndt et al, 2004;O'Neill, 2002;Olsson and Sundler, 2006).…”
Section: Introductionmentioning
confidence: 99%